THEORIES OF CAUSAL CONNECTION IN THE SCIENCE OF CRIMINAL LAW - Кубальський, Владислава Нарцизович; Браславець, Ксенія Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to define the essence and features of the basic theories of causal connection in the science of criminal law for their application in law enforcement activities in the qualification of crimes. Methods of research: the methodological basis of the research are general scientific and special-scientific methods of cognition, in particular dialectical, dogmatic (formal-logical), historical-legal and comparative-legal. Results: it is determined that the optimal for criminal law is the theory of necessary induction, which allows taking into account the specifics of certain categories and syllables of crimes and considers the concrete, real-life dependence of phenomena, within which the consequence, with an internal necessity, is caused by an act. Discussion: in our time, the pre-trial investigation bodies focus on the establishment of causal links, which leads to mistakes in the classification of crimes, as well as the jurisprudence on this issue is not unified, and the presence of often causal connection in most cases is simply suppressed. Therefore, it actualizes the need to study theories of causal communication through which law enforcement agencies could actually establish the presence or absence of a legally significant causation in a particular criminal proceeding. Consequently, the notion of causal connection is of particular importance for legal science and allows the most complete reflection of the social danger of a crime, since it combines such elements of social danger as «action» and «consequence». The list of existing theories of causation in the science of criminal law is not exhaustive. The considered theories are based on various methodological principles, which makes it possible to use them to establish different types of causal connection. It should be noted that researchers do not make a clear distinction between causation and other types of objective communication. However, in our opinion, in practice, the most appropriate is to apply the theory of necessary induction. Legal significance in the context of criminal legal consequences has only the necessary and internally determined causation. Since the features of establishing the causal connection are different in different crimes, its characteristics must be formulated taking into account the objective features of each of them.